Web-Based Data Information System for Students and Teachers at Al-Qur’an Education Parks in Kasihan, Bantul - Teuku Syauqi Maulana; Haris Setyawan; Asroni Asroni (Emerging Information Science and Technology, 2021)
Al-Qur’an Kindergarten (TKA) and Al-Qur’an Education Park (TPA) are non-formal religious education institutions emphasizing studying Islamic values. The development of society necessitates institutions that hold TKA/TPA-related information promptly and correctly. Currently, technology is required to aid an institution in maintaining data and providing TKA/TPA-related information. The data information system aims to provide data for the TKA/TPA coordination agency and ensure the implementation of the administrative order to assure the operational and development sustainability of the IT-based TKA/TPA operating regions. This research intends to develop a web-based information system that can handle the data of students and teachers to reduce the number of errors due to manual data management. A web-based application system for student and teacher data information in TPA in Kasihan was developed utilizing the CodeIgniter framework, the Hypertext Preprocessor (PHP) programming language, the MySQL database, the SDLC method, and the Prototype model. Due to its superiority, the website was selected as the application’s foundation since it is lightweight and could be accessed rapidly using a web browser and an internet or intranet connection to the server. This study has produced a web-based application constructed successfully and could be utilized as a data information system for TPA students and teachers in Bantul.